The study of turkishisms in world languages (Eurasian Journal of Philology Science and Education, 2023)
There is a discussion of the problem of Turkisms in foreign languages, the phonetic change of sounds in foreign languages, as well as specific examples. A comparative historical method and data comparison methods are used for studying Turkisms in foreign languages.Turkish linguistics has interested in sociolinguistic language relations. Since ancient times, researchers have been concerned with the origin of world languages. The origin of world languages has been disputed; some scientists believe they arose through the mixing of dialects. In order to solve this problem, it is necessary to study the language itself and identify its phonetic features.Chinese and Turkic peoples were in close contact according to the earliest rock writings. Orkhon-Yenisei written monuments reveal this. Turks often contacted with Sogdians, Arabs, Persians, Mongols and borrowed words from their languages, just as these peoples borrowed many Turkic words into their languages. As a result of close contacts between peoples, there is an interchange between their languages.There are foreign elements in the lexical fund of the Turkic languages. The same applies to the Turkisms. Due to linguistic data, from a scientific point of view, it can be proved that Turkisms are used in foreign languages. In modern Turkish terminology, the term alıntı is used to refer to borrowed foreign vocabulary in Turkic languages, the term verinti to refer to borrowed Turkic vocabulary in foreign languages. In the modern Kazakh language there is no equivalent for the term verinti. According to the scientific literature, Arabicisms and Farsisms are borrowed vocabulary, while European words and terms are called foreign vocabulary due to the lack of an equivalent in the source language.Keywords: Turkic studies, Turkic languages, foreign languages, foreign words, Turkisms, language interrelations.